Subsurface waste heat recovery from the abandoned steam assisted gravity drainage (SAGD) operations. (1st October 2022) - Wei, Cao; Nawaz, Ayesha; Nath, Devjyoti; Zirrahi, Mohsen; Hassanzadeh, Hassan
Abstract: A considerable fraction of the energy injected during the thermal recovery of oil remains in the subsurface and wasted in the surrounding geological formations after the profitable life of oil wells is over. This work studied the concept of thermal energy extraction from the abandoned SAGD operations in oil sands reservoirs for generating electric power. The cold water is injected as a working fluid to extract heat after the oil production is ceased, and the produced hot water is fed to a surface binary cycle to generate electric power. The results show that an oil sands reservoir after SAGD operations could be regarded as an artificial geothermal system suitable for thermal energy extraction. It is demonstrated that a total net electric energy output of 57 GWh could be achieved based on a single SAGD well pair during a ten-year heat-extraction time, indicating the huge heat extraction potential at full field scale. The results show that the thermal energy conversion efficiency to electricity for the abandoned SAGD wells can reach as high as 12%. The demonstrated subsurface waste heat recovery from the abandoned SAGD sites revealed that between 15 and 36% reduction in CO2 emission could be achieved. Graphical abstract: Image 1 Highlights: Abandoned SAGD sites can be converted to artificial geothermal loops. Potential of this novel concept based on a single SAGD well pair is demonstrated. 8–15 kWh energy per unit bulk volume of oil sands reservoir can be recovered. Conversion efficiency of heat to electricity is between 6 and 12%. 15–36% CO2 emission reduction and 7–18 /ton carbon tax recovery can be achieved.